2017
DOI: 10.1093/ptj/pzx090
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Integrate Health Promotion and Wellness in Physical Therapist Practice: Development and Validation

Abstract: An interdisciplinary group of health professionals believes that physical therapists should practice health-focused care and that the HFPTM is a valid model. This model could help physical therapist educators when educating physical therapist students and clinicians to practice health-focused care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 18 publications
0
43
0
5
Order By: Relevance
“…e literature suggests that acquiring roles related to prevention and health promotion requires extending the service beyond the acute care setting, towards secondary care and community settings [28]. It is also suggested that physical therapy service delivery should adopt a model that integrates health promotion and prevention in daily practice [28,29]. e Council on Prevention, Health Promotion, and Wellness [30] indicated that physiotherapists should have the knowledge, skills, and competencies relevant to health promotion and prevention.…”
Section: Service Encompass a Variety Of Clinical Responsibilities Refmentioning
confidence: 99%
“…e literature suggests that acquiring roles related to prevention and health promotion requires extending the service beyond the acute care setting, towards secondary care and community settings [28]. It is also suggested that physical therapy service delivery should adopt a model that integrates health promotion and prevention in daily practice [28,29]. e Council on Prevention, Health Promotion, and Wellness [30] indicated that physiotherapists should have the knowledge, skills, and competencies relevant to health promotion and prevention.…”
Section: Service Encompass a Variety Of Clinical Responsibilities Refmentioning
confidence: 99%
“…Notes. (THR, TKR)* = total hip replacement, total knee replacement; 1 multiple answers possible; 2 were sent to represent the head of the department; 3 in Germany, this refers to the education of Sport und Bewegungstherapie.…”
Section: Samplementioning
confidence: 99%
“…Second, in general, PAP is not historically established and is a relatively young topic for exercise therapy. Related frameworks[1,2] and concepts mentioned above for PAP in exercise therapy were only developed and published during this century. A highly quoted statement claims that it takes 17 years to apply 14% of research evidence to reach clinical practice…”
mentioning
confidence: 99%
“…Faculty in the School of Health Professions at the University of Alabama at Birmingham (UAB) developed and validated a practice model for use of HFC in rehabilitation clinical practice. The UAB HFC model is useful for educational purposes, and is particularly useful for exploring clinical decision-making and application of HFC to patient/client cases [ 35 ]. Major steps in the model include (1) performing a needs analysis for HFC, (2) determining a patient’s/client’s need for lifestyle behavior change (LBC), (3) collaborating with patient/client about LBC needs, (4) providing LBC interventions, and (5) assessing LBC outcomes.…”
Section: Recommended Curricular Contentmentioning
confidence: 99%
“…Major steps in the model include (1) performing a needs analysis for HFC, (2) determining a patient’s/client’s need for lifestyle behavior change (LBC), (3) collaborating with patient/client about LBC needs, (4) providing LBC interventions, and (5) assessing LBC outcomes. More details about specific strategies can be found in reference [ 35 ].…”
Section: Recommended Curricular Contentmentioning
confidence: 99%